Determination of trace uranyl in saline samples using chelation ion chromatography - Paull, B; Haddad, PR (Analytical Communications, 1998)
A liquid chromatographic method for the determination of trace levels of UO22+ in highly saline samples has been developed. A polystyrene divinylbenzene reversed-phase column was impregnated with methylthymol blue, resulting in a chelating stationary phase. An isocratic method, using a 0.5 M KNO3, 40 mM HNO3 eluent, allowed the direct injection of up to 0.2 ml of a saline sample, with UO22+ eluting away from the sample matrix peak in under six minutes. The development of an eluent step gradient procedure, using a step up from 6 mM HNO3 to 60 mM HNO3, allowed sample injection volumes of up to 2 ml without substantial peak broadening and resulted in a detection limit for UO22+ of less than 1 g l1, in samples containing massive excesses of matrix metals. The procedure was applied to the determination of trace UO22+ in a saturated saline Antarctic lake sample. The results obtained compared well with those obtained using ICP-MS.